2022
DOI: 10.1101/2022.02.04.477749
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Sensory Schwann cells set perceptual thresholds for touch and selectively regulate mechanical nociception

Abstract: That sensory neurons alone transduce mechanical stimuli was challenged by the discovery of nociceptive Schwann cells that can initiate pain. Consistent with the existence of inherently mechanosensitive sensory Schwann cells, we found that mechanosensory function of almost all nociceptors, including those signaling fast pain were critically dependent on sensory Schwann cells. Furthermore, in polymodal nociceptors, sensory Schwann cells signal mechanical, but not cold or heat pain. Terminal Schwann cells also su… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 49 publications
(54 reference statements)
1
13
0
Order By: Relevance
“…Additionally, there is now evidence that sensory neuron mechanosensitivity may not be solely dependent on channels within the sensory cell membrane. Thus, recently identified specialized Schwann cells that surround the peripheral endings of unmyelinated nociceptors may directly participate in the detection of noxious mechanical stimuli ( Abdo et al, 2019 ; Ojeda-Alonso et al, 2022 Preprint ). In addition, cells that form specialized sensory end-organs innervated by mechanoreceptors in birds were also recently shown to be mechanosensitive ( Nikolaev et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, there is now evidence that sensory neuron mechanosensitivity may not be solely dependent on channels within the sensory cell membrane. Thus, recently identified specialized Schwann cells that surround the peripheral endings of unmyelinated nociceptors may directly participate in the detection of noxious mechanical stimuli ( Abdo et al, 2019 ; Ojeda-Alonso et al, 2022 Preprint ). In addition, cells that form specialized sensory end-organs innervated by mechanoreceptors in birds were also recently shown to be mechanosensitive ( Nikolaev et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Meissner corpuscles endow humans with the remarkable ability to manipulate objects and tools, and enable tactile specialist birds to carry out a multitude of foraging behaviors 5,7,[22][23][24][25] . Whether mammalian LCs are mechanosensitive remains to be determined, but appears likely given that dissociated murine Schwann cells are mechanosensitive in culture 10,11 .…”
Section: Discussionmentioning
confidence: 99%
“…Although morphologically and functionally diverse, these end organs invariably contain terminal Schwann cells (TSC) that form close interactions with mechanoreceptor afferent terminals. The afferents, which express mechanically gated ion channels such as Piezo2 8,9 , are considered to be the only touch-sensing elements within these end organs, but recent work has revealed that dissociated mouse Schwann cells display mechanosensitivity in culture 10,11 .…”
Section: Main Textmentioning
confidence: 99%
“…Although morphologically and functionally diverse, these end organs invariably contain terminal Schwann cells (TSC) that form close interactions with mechanoreceptor afferent terminals. The afferents, which express mechanically gated ion channels such as Piezo2 (4,5), are considered to be the only touch-sensing elements within these end organs, but recent work has revealed that dissociated mouse Schwann cells display mechanosensitivity in culture (6,7). Moreover, mammalian Meissner corpuscles and their avian analogs (historically called corpuscles of Grandry and referred to here as avian Meissner corpuscles) contain TSCs known as lamellar cells (LCs) (8,9), which fire mechanically activated action potentials (APs) in intact avian Meissner corpuscles in situ (10).…”
Section: Introductionmentioning
confidence: 99%